TNF-α, NF-kb and NLRP3 in Relation to Tumor Development - Li, Shujian (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the development of society, cancer has become one of the major diseases with a high incidence and fatality rate in the world.Scientists have proved that TNF-α,NF-kb and NLRP3 plays an important role in the tumor microenvironment (TME), especially their dual effects in regulating inflammation and tumor progression. However, there is still a lack of a comprehensive understanding of the specific mechanisms of these molecules in different tumor types and their interactions, which also limits their potential application in tumor immunotherapy. Therefore, the study of the relationship between inflammatory factors and tumor development has become a hot topic in today's society. For example, the inflammatory factor TNF-α secreted by NF cells and T cells can directly annihilating tumor cells, and can indirectly kill tumor cells by activating the immune system’s response, NF-kb and NLRP3 also inhibit tumor growth, invasion and metastasis under specific conditions. In conclusion, inflammatory cytokines are closely related to the development of tumors, and this study also provides a solid foundation for future immunotherapy of tumors. This article focuses on the promotion and inhibition effects of inflammatory factors TNF-α, NF-kb and inflammatory body NLRP3 on tumors, providing evidence and conclusions for researchers.